PBL in the first year of an industrial engineering and management program: a journey of continuous improvement - Alves, Anabela C. (2019)
The Integrated Master Degree in Industrial Engineering and Management (IEM) at the School of Engineering of the University of Minho has been introducing Project-Based Learning (PBL) since the year 2004 and it is now in its 14th edition. This is a long time-frame that allowed to consolidate the model. Nevertheless, there is always space for improvement, considering that this learning process is evaluated every year by both teachers and students, in an open and critical free thinking environment. Based on this, it is time to understand the main changes that have happened over the years, since the first implementation. Studying the entire time-frame is a titanic task, so the authors decided to present, for the purpose of this paper, only the changes for the period of 2010-11 to 2016-17 (i.e. seven editions) applied in the PBL model of the first year of the IEM program. The main aspects that will be compared along the different editions will be the courses involved, the coordination team, the inclusion of the project in each course’s curriculum, the number and type of tutors involved, the assessment model and the miles tones considered. A document analysis, the authors’ own experiences and the previous results from PBL evaluation surveys carried out to students are the main methods for data collection. The results show that the PBL model in the IEM program is being refined and adapted in order to promote, not only the best learning experiences for students, but also their continuous motivation to learn. Despite the good results achieved, a greater effort is needed.